AN OVERVIEW OF PHONETICS, PHONEMICS, AND GRAPHEMES - Ibnu Dwi Naqsyah; Fadhilatul Husna (Jurnal Recoms, 2024)
Phonetics explores how humans produce speech sounds, focusing on their physical creation and articulation. Phonemics, a subset of phonology, examines how sounds function within a language, particularly their role in distinguishing meaning. Graphemes, on the other hand, are the smallest meaningful units of written language that can differentiate words. This research aims to delve into the interaction between spoken sounds and written symbols and their contribution to linguistic communication. The study employs a descriptive qualitative approach, analyzing data from books, journals, and other relevant literature on phonetics, phonemics, and graphemics. Data collection involves library research and content analysis, which are interpreted to understand the production of language sounds, their role in conveying meaning, and their representation in writing. Findings indicate that phonetics focuses on sound production, phonemics deals with sound units such as phonemes and their variations (allophones), and graphemics examines a language's writing system, including its basic units (graphemes). In conclusion, phonetics, phonemics, and graphemics are interconnected branches of linguistics that collectively address the role of sounds and symbols in communication.